2013
DOI: 10.1590/s0080-623420130000500030
|View full text |Cite
|
Sign up to set email alerts
|

The use of the quality model of Parasuraman, Zeithaml and Berry in health services

Abstract: RESUMOTrata-se de um artigo teórico acerca do modelo de avaliação de qualidade em serviços de saúde proposto por Parasuraman, Zheitaml e Berry, a fim de mensurar o grau de satisfação de usuários. Tal modelo baseia-se na análise de expectativas e percepções de usuários de serviços de saúde, por meio de cinco dimensões: tangibilidade, confiabilidade, responsividade, garantia e empatia. Da diferença entre o que é esperado pelo usuário e o serviço oferecido derivam os gaps, ou lacunas, que podem ser o principal ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0
39

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 5 publications
0
48
0
39
Order By: Relevance
“…The SERVQUAL technique, designed by Parasuraman et al (13), is one of the best techniques for evaluating customers' expectations and perceptions of service quality (1, 2), and includes five dimensions: tangibles, reliability, responsibility, empathy, and assurance (4,14). Curiand Sinkler (2002) showed that there was a gap in the quality of the studied rehabilitation centers, and highlighted reliability and empathy as important dimensions (13).…”
Section: Introductionmentioning
confidence: 99%
“…The SERVQUAL technique, designed by Parasuraman et al (13), is one of the best techniques for evaluating customers' expectations and perceptions of service quality (1, 2), and includes five dimensions: tangibles, reliability, responsibility, empathy, and assurance (4,14). Curiand Sinkler (2002) showed that there was a gap in the quality of the studied rehabilitation centers, and highlighted reliability and empathy as important dimensions (13).…”
Section: Introductionmentioning
confidence: 99%
“…12,13 A professional satisfaction is an important indicator of quality in the size of organizational results. [2][3] In Accreditation methodology, including international, where quality is known as the essential purpose, 4,6,8 aggregating satisfaction with human capital can be a valuable weapon within the scope of qualified assistance.…”
Section:  Accreditation: Encouraging the Practice Of Continuing Educmentioning
confidence: 99%
“…2 Thus, systematic evaluation processes can generate important information for decision-making that underlies the continuous improvement of care. 3 The evaluation of health quality has the potential to link organizations' proposals to the satisfaction of their clients, [2][3] however, it is a complex managerial and contingent action, which is related to the service's resoluteness, in line with the evolution of the In this sense, the evaluation of hospital quality has gained international representativeness by the system known as Acreditação. 2,4 When considering that the elucidation of issues related to International Accreditation can foster discussions about the adhesion of this system by Brazilian institutions, the question is: How is International Accreditation perceived by the professionals who live it?…”
mentioning
confidence: 99%
“…1,2 Apesar da gama de ferramentas e instrumentos, postula-se que na busca pela qualidade dos serviços de saúde por meio da ação gerencial, a avaliação é ferramenta indispensável e indissociável ao almejo do cuidado qualificado, por se tratar de um mecanismo contínuo e sistemático de identificação de fatores que alicerçam a tomada de decisão em prol de melhorias. 2,3 Na avaliação para a melhoria da qualidade dos serviços de saúde, tem-se dado amplo destaque ao emprego dos indicadores, que se conformam como uma unidade de medida de uma atividade à qual está relacionado. 4 Ou, ainda, como uma medida qualitativa ou quantitativa que pode ser usada como um guia para monitorar e avaliar a qualidade assistencial e as atividades de um serviço.…”
Section: Introductionunclassified